Integration of Artificial Intelligence in Microteaching and it’s Impact on Self-Confidence and Anxiety in Teaching Students - Laila Fitria Ulma; Nazwa Devina Hoerunnissa; Netriwati Netriwati; Anita Humaida Kulsum; Fadly Nendra (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
In this study, the integration of AI in microteaching was operationalized through the use of AI-based technologies in lesson planning, instructional material development, teaching practice simulations, and automated feedback provision. However, mathematics education students still face psychological challenges, particularly related to self-confidence and teaching anxiety during teaching practice. This study aimed to analyze the relationship between AI integration in microteaching and the teaching self-confidence and teaching anxiety of mathematics education students. The research employed a quantitative approach with an ex post facto design and involved 103 students from the Mathematics Education Study Program at UIN Raden Intan Lampung as respondents. Data were collected through questionnaires and analyzed using statistical software through two separate simple linear regression models, namely to examine the relationship between AI integration (X) and teaching self-confidence (Y₁), and between AI integration (X) and teaching anxiety (Y₂). The results showed that AI integration had a positive and significant relationship with teaching self-confidence, with a coefficient of determination of R² = 0.414. In contrast, AI integration demonstrated a negative and significant relationship with teaching anxiety, with a coefficient of determination of R² = 0.088. The novelty of this study lies in its examination of AI integration in microteaching by simultaneously investigating the aspects of teaching self-confidence and teaching anxiety among prospective mathematics teachers. The findings imply that the utilization of AI in microteaching can support the pedagogical and psychological readiness of prospective teachers in the context of 21st-century education.